Perbanyakan Nematoda Patogenik Serangga (Rhabditida: Steinernema dan Heterorhabditis) pada Media In Vitro Cair Statik - Chaerani Chaerani; M. Ace Suhendar; J. Harjosidarmop (Jurnal AgroBiogen, 2012)
Entomopathogenic nematodes belongingto genera Steinernema and Heterorhabditis are potentiallymost effective and safe biological control agents for insectpests, especially for soil dwelling insects and those living incryptic habitats. Field application of the nematodes is stillhampered by supply of large number of infective juvenile(IJ) nematodes. Five published in vitro media along with itstwo modifications were tested for mass propagations of twoindigenous nematodes (H. indicus PLR2 and SteinernemaT96) and one commercial strain (S. carpocapsae #25).Varying levels of IJ yields were observed across thereplications and experiments. Medium F that contained 1.0%yeast extract, 2.5% egg yolk, and 4.0% soy oil yielded thehighest IJ numbers of H. indicus PLR2 (1.5×105 IJ ml-1) andof S. carpocapsae #25 (2.9×105 IJ ml-1), whereas the widelyused medium B, which is based on homogenized chickenoffal (40%), yielded the highest number of Steinernema T96(5.8×104 IJ ml-1). The IJ’s quality, as measured by theirmorphometrics and pathogenicities, were generallyimpaired, indicating the lack of essential nutrient(s) in themedia. Optimization of the propagation media is thereforestill needed to increase IJ’s quantity and quality to achievethe required standard for commercial scale of artificialpropagation.